Optimasi Komposisi Makanan Diet bagi Penderita Hipertensi menggunakan Algoritme Genetika - Muhammad Shafaat; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Hypertensive is one of the main causes of mortality and morbidity in Indonesia. as the result that, the clinical problems of the disease that is interventions which at various levels of health facilities are commonly done. For people with hypertension should be arranging their food menu to avoid and confine foods that can increase blood pressure. Therefore, it needed a diet to control the blood sugar levels in hypertensive patients by regulating the composition of the diet. One of techniques that is used to manage regulate the composition of diet foods for hypertensive patients used by genetic algorithm approach. The genetic algorithm process uses the representation of the integer with the length of chromosome 105, each gene of the population is the food number in each group and each index with multiples 15 represents of the day, The crossover method that is used the extended intermediate crossover, while the mutation method that is used reciprocal exchange mutation, and the selection method with elitsm selection. The optimal parameter results obtained on the test population number is 80 with the fitness value 1100.495433, the number of generations is 300 with the fitness value 1190.022286, and the combination of cr and mr is 0.1 and 0.9 with the fitness value 1150.466927. The results of the solution given in the form of food menu recommendations for few days for morning, noon, and night time and with minimal cost.